2010
DOI: 10.1186/1476-4598-9-278
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib reduces FAK phosphorylation increasing the effects of RPI-1 inhibition in a RET/PTC1-expressing cell line

Abstract: BackgroundTPC-1 is a papillary thyroid carcinoma (PTC)-derived cell line that spontaneously expresses the oncogene RET/PTC1. TPC-1 treated with the RET/PTC1 inhibitor RPI-1 displayed a cytostatic and reversible inhibition of cell proliferation and a strong activation of focal adhesion kinase (FAK). As dasatinib inhibition of Src results in reduction of FAK activation, we evaluated the effects of TPC-1 treatment with dasatinib in combination with RPI-1.ResultsDasatinib (100 nM) strongly reduced TPC-1 proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 38 publications
5
48
1
1
Order By: Relevance
“…The role of the FAK pathway has recently been suggested to be important in PTC and ATC. Schweppe et al (14) characterized the antitumor effects of AZD0530, in PTC and ATC cells providing the first evidence that FAK is phosphorylated in a subset of PTC tumor samples (15,16). Our results showed that a different Tyrosine residue on FAK (Tyr 576/577) from that found in the study by Schweppe et al was phosphorylated in thyroid cancer (14).…”
contrasting
confidence: 32%
“…The role of the FAK pathway has recently been suggested to be important in PTC and ATC. Schweppe et al (14) characterized the antitumor effects of AZD0530, in PTC and ATC cells providing the first evidence that FAK is phosphorylated in a subset of PTC tumor samples (15,16). Our results showed that a different Tyrosine residue on FAK (Tyr 576/577) from that found in the study by Schweppe et al was phosphorylated in thyroid cancer (14).…”
contrasting
confidence: 32%
“…Aberrant expression or activation of Src family kinases causes perturbations in these activities, leading to transformation and progression of malignant disease (17). Endogenous Src kinases have been shown to promote invadopodium formation in response to growth factors and chemokines.…”
Section: Together These Results Indicate That Ecti Inhibits the Invamentioning
confidence: 99%
“…PTC cell lines (TPC-1 and K1) were seeded on 100-mm tissue culture plates, incubated for 18 h, then treated with drugs for 0, 12, 24, 48, or 72 h. Next, FACS analysis was performed as previously described (Caccia et al 2010).…”
Section: Facs Analysismentioning
confidence: 99%
“…performed as previously described (Caccia et al 2010). PTC and ATC cells were stained with fluorescent phalloidin (Sigma-Aldrich) for visualizing the cytoskeleton, with diamidino-2-phenylindole (DAPI) (Biostatus Limited, Leicestershire, UK) as a nuclear marker, with anti-b-tubulin (Sigma-Aldrich) for visualizing microtubules organization and with anti-phospho-histone H3 (S10) (Abcam, Inc.) for visualizing histone H3.…”
Section: Cell Culture and Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation